An Analysis of Association Between Nasal Bone Morphology and Sinonasal Anatomical Variations. Issue 1 (January 2020) - Kuzucu, Ihsan; Parlak, Selcuk; Baklaci, Deniz; Guler, Ismail; Sakalli, Cemal; Mendi, Ahmet Bokebatur; Kum, Rauf Oguzhan; Ozcan, Muge
Abstract : Abstract: The goal of this study was to investigate the association between various sinonasal anatomical variations and the morphological features of lateral nasal bone, using paranasal computerized tomography (PNCT) sections. Two hundred and fifty patients who underwent a PNCT scan because of a prediagnosis of nasal septum deviation or sinusitis were included in the study. For each patient, presence of the following anatomical variations was determined on CT sections: length and thickness of nasal bone, thickness of intermediate nasal bone, pneumatized middle turbinate, paradox middle turbinate, Agger nasi cell, Haller cell, Onodi cell, supraorbital cell, pneumatized uncinate process, and nasal septal deviation. The effect of each anatomical variation on the length and thickness of the lateral nasal bone was investigated. The patients with bilateral pneumatized middle turbinate and the patients with bilateral Agger nasi cell had a thinner lateral nasal bone both on the right and the left sides compared to those without. The patients with bilateral Onodi cell and Agger nasi cell had a longer lateral nasal bone both on the right and the left sides compared to those without. The nasal bone thickness was significantly thicker on the deviation side than the contralateral nasal bone. The nasal bone length was significantly longer on the side of the septum deviation. In this study, we found that sex, presence of Agger nasi and Onodi cells, pneumatization of middle turbinate, and direction of nasal septal deviation influenced the morphology of the nasal bone. For successful nasal surgery, careful examination of preoperative anatomical variations is very important. Abstract : Supplemental Digital Content is available in the text